2010
DOI: 10.3341/kjo.2010.24.5.291
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Korean Patients with Congenital Aniridia

Abstract: PurposeTo investigate the clinical features of Korean patients with congenital aniridia.MethodsThis retrospective study focused on 60 eyes from 31 patients who were diagnosed with congenital aniridia at Kangnam St. Mary's Hospital from 1996 to 2007. Patient age, gender, visual acuity (VA), family history, and previous ocular history were recorded. The presence of keratopathy, glaucoma, cataract, foveal hypoplasia, and other ocular or systemic anomalies were evaluated for each patient.ResultsThe proportion of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 18 publications
5
23
0
1
Order By: Relevance
“…The clinical findings presented here corroborate what has been presented in literature regarding the broad spectrum of the ocular phenotype and the extent of intrafamilial and individual variability (1,2,4,8). In the family studied for this investigation, different degrees of iris hypoplasia (from total aniridia to misshapen pupil) were observed within family members and between the eyes of an affected individual, with the analyzed affected individuals presenting severe, progressive loss of vision.…”
Section: Discussionsupporting
confidence: 88%
“…The clinical findings presented here corroborate what has been presented in literature regarding the broad spectrum of the ocular phenotype and the extent of intrafamilial and individual variability (1,2,4,8). In the family studied for this investigation, different degrees of iris hypoplasia (from total aniridia to misshapen pupil) were observed within family members and between the eyes of an affected individual, with the analyzed affected individuals presenting severe, progressive loss of vision.…”
Section: Discussionsupporting
confidence: 88%
“…Cataract is common in aniridia, with over 90% prevalence in our cohort, similar to a Korean cohort with 60 eyes where 88% had cataract or were operated for cataract (Park et al. 2010 ). Cataract prevalence in aniridia in the literature varies from 50 to 85% (Nelson et al.…”
supporting
confidence: 87%
“…2009 ; Park et al. 2010 ; He et al. 2012 ), the timing and detailed phenotype of cataract in aniridia have not been well described.…”
mentioning
confidence: 99%
“…Six eyes (32% of those with ocular hypertension, 40% of those who received cataract surgery) developed secondary ocular hypertension after intraocular surgeries. Park et al [ 21 ] also reported that deterioration of glaucoma was the main postoperative problem and was observed in 50% of patients after cataract surgery. Therefore, it is important to prepare for and manage secondary ocular hypertension after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%